2009
DOI: 10.4081/1224
|View full text |Cite
|
Sign up to set email alerts
|

The role of immunohistochemistry in the diagnosis of hyalinizing clear cell carcinoma of the minor salivary gland: a case report

Abstract: A case of hyalinizing clear cell carcinoma (HCCC) of the minor salivary glands of the oral cavity is reported. A 52- year-old woman presented with a growing mass at the base of the tongue. The patient underwent complete resection of the tumour. The histological picture was characterized by trabeculae or solid nests of proliferating cells with a clear cytoplasm, surrounded by a hyalinizing stroma. Tumour cells were immunoreactive for Cytokeratins 5, 6, 7, 8, 14, 17 and 18. No reactivity was observed for cytoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…29 In this study, we did not observe a significant immunoreactivity for Tβ 4 in intratumoral and in peritumoral vessels: Tβ 4 was always expressed in the cytoplasm of tumor cells, in the absence of any reactivity in the connective tissue, as previously reported by our group in developing human organs. 32,33 Outside the tumor cells, Tβ 4 immunostaining was restricted to peritumoral and intratumoral mast cells, a finding already reported in salivary gland tumors 34 and in human skin. 35 Another intriguing finding in our study is the observation of a progressive decrease in the expression of E-cadherin on the cell surface in Tβ 4 -reactive tumor cells undergoing EMT, with disappearance of E-cadherin in isolated spindle tumor cells migrating toward lymphatic and/or blood vessels.…”
Section: Discussionsupporting
confidence: 60%
“…29 In this study, we did not observe a significant immunoreactivity for Tβ 4 in intratumoral and in peritumoral vessels: Tβ 4 was always expressed in the cytoplasm of tumor cells, in the absence of any reactivity in the connective tissue, as previously reported by our group in developing human organs. 32,33 Outside the tumor cells, Tβ 4 immunostaining was restricted to peritumoral and intratumoral mast cells, a finding already reported in salivary gland tumors 34 and in human skin. 35 Another intriguing finding in our study is the observation of a progressive decrease in the expression of E-cadherin on the cell surface in Tβ 4 -reactive tumor cells undergoing EMT, with disappearance of E-cadherin in isolated spindle tumor cells migrating toward lymphatic and/or blood vessels.…”
Section: Discussionsupporting
confidence: 60%
“…Our review of the literature revealed 130 cases of HCCC among 48 articles . We did exclude a number of articles that have been reported by others to represent HCCC but, in our view, did not provide sufficient histologic description to confirm the diagnosis .…”
Section: Resultsmentioning
confidence: 98%
“…Mucicarmine stain can be very helpful for highlighting the mucocytes and distinguishing them from the other clear cells. [4]…”
Section: Discussionmentioning
confidence: 99%